Comparison of aggregation-induced emission enhancement effect between π-σ* and σ-σ* conjugation on silole and application in explosives detection. (May 2022) - Haque, Md Hasanul; Sohn, Honglae
Abstract: Herein we have synthesized and characterized the novel π-σ* conjugated 1, 4-bis(1-methyl-2, 3, 4, 5-tetraphenyl-1-silacyclopentadienyl)benzene nanoaggregates based on aggregation-induced emission enhancement (AIEE) property for the detection of nitroaromatic compounds by fluorescence quenching. The new photoluminescent silole nanoaggregates exhibited unique AIEE property by increasing the emission intensity 180 times in THF/water mixtures. We investigated that the π-σ* hyper conjugation of Si–C phenyl ring is more effective on AIEE due to the less non-radiative decay than the σ-σ* hyper conjugation of Si–Si bond of 1, 4-bis(1-methyl-2, 3, 4, 5-tetraphenyl-1-silacyclopentadienyl). The π-σ* conjugated nanoaggregates showed excellent sensitivity for sensing explosives. High Stern-Volmer constant was observed during quenching of photoluminescence (PL) intensity upon adding explosives. The absolute quantum yield and average particle size were measured for the nanoaggregates and tuned by controlling at different fraction of water. These results demonstrate that AIEE property of π-σ* conjugated silole nanoaggregates will provide guidance to develop fluorescent materials for detecting explosives. Graphical abstract: Image 1 Highlights: Two different types of conjugated siloles were synthesized. Comparison study between π-σ* and σ-σ* hyper conjugation of silole. Both siloles showed great aggregation-induced emission enhancement (AIEE) property. The π-σ* conjugated exhibited 180 times higher photoluminescence enhancement. These nanoaggregates showed excellent sensitivity to detect explosives.